أثر التفسير الجغرافي للسيرة النبوية في القرآن الكريم في الترجيح بيـن أقوال المفسرين: The Impact of Geographical Interpretation of Prophetic Sīrah on Resolving Differences Amongst Qur’anic commentators - RABABA’H محمد مُجلّي أحمد ربابعة (الدراسات الإسلامية, 2025)
This study examines the influence of geographical context on interpreting the Holy Qur’an, particularly the locations where the Prophet Muhammad’s (Peace be upon him) Sīrah unfolded. By examining classical and contemporary Qur’anic commentaries, the research identifies instances where geographical features have led to interpretative differences, focusing on key events such as the battles of Badr, Uḥud, and the Trench, the conquest of Makkah, the rites of Hajj, and the description of the Cave of Thawr. The study employs a comparative and analytical approach, correlating exegetical perspectives with the observable geographical realities of these sites, aided by photographs and videos available online. One of the primary findings is that the geographical interpretation of the Holy Qur’an is a significant principle in resolving exegetical discrepancies and a valuable tool for enhancing semantic understanding within Qur’anic studies.